2020
DOI: 10.1016/j.najef.2019.101140
|View full text |Cite
|
Sign up to set email alerts
|

The role of credit supply shocks in pacific alliance countries: A TVP-VAR-SV approach

Abstract: La carrera universitaria suele ser muy difusa cuando no hay un horizonte al cual deseas llegar o cuando no hay un motor de inspiración para avanzar. Viví de esta manera la mayor parte de mi carrera, hasta que tuve la suerte de conocer al profesor Gabriel Rodríguez y pude encaminarme hacia la ruta de la investigación. Estimado profesor, como siempre suelen iniciar mis correos, quisiera darle mis más profundos agradecimientos por guiarme, apoyarme y corregirme en mi formación como economista. Quiero darle las gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…Future research could consider alternatives such as non-recursive identifications, as suggested by Quispe (2001), or sign restrictions as detailed in Guevara and Rodríguez (2020). Including additional variables could enhance the identification of shocks and MP transmission channels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Future research could consider alternatives such as non-recursive identifications, as suggested by Quispe (2001), or sign restrictions as detailed in Guevara and Rodríguez (2020). Including additional variables could enhance the identification of shocks and MP transmission channels.…”
Section: Discussionmentioning
confidence: 99%
“…Including additional variables could enhance the identification of shocks and MP transmission channels. For instance, credit variables like loan supply could enhance credit channel visibility, as shown in Viladegut and Cabello (2014) and Guevara and Rodríguez (2020). Furthermore, the identification of MP shocks could be improved by incorporating other BCRP instruments, as proposed by Lahura (2010), Castillo et al (2011), andRodriguez et al (2021).…”
Section: Discussionmentioning
confidence: 99%
“…Guevara and Rodriguez [26] applied the same methodology in case of Pacific Alliace countries and found that loan supply shocks are important drivers of economic growth and their contribution is dynamic and heterogeneous among the selected countries.…”
Section: Literature Reviewmentioning
confidence: 99%
“…On the other hand, the Pacific Alliance (PA) is a regional integration initiative, which was announced in Lima (Peru) on April 28, 2011, through the Lima Declaration made up of four member countries: Chile, Colombia, Mexico, and Peru, four countries in the incorporation process, four associated countries, and more than 40 observer countries on four continents [7]. PA presents four main axes as vision being: more integrated, more global, more connected, and more citizen.…”
Section: Introductionmentioning
confidence: 99%
“…PA presents four main axes as vision being: more integrated, more global, more connected, and more citizen. The last vision englobes to achieve the SDGs and ensure that the benefits of the PA reach all citizens, contributing to overcoming inequality and poverty, and have a sustainable agenda with joint projects for the adaptation and mitigation to the effects of climate change and energy clean, among others [7].…”
Section: Introductionmentioning
confidence: 99%